Ruptures, renaissances et continuités. Modes de construction de l’histoire de l’art maghrébin - Annabelle Boissier; Fanny Gillet (L’Année du Maghreb)
This article proposes a comparative study of the history of visual arts in Algeria and Tunisia from the 1960s to the 1980s. By drawing on texts produced in the wake of Algerian and Tunisian independence (e.g. exhibition catalogues published in-country or abroad, monographs and essays on art history) we aim at analysing the shaping and evolution of discourses regarding art within two culturally close countries. If an initial assessment leads to an identification of common issues in each case, a more detailed study of sources allows us to reveal differences relating to their particular histories. This study also questions the homogeneity of reference works produced since the 1980s and how a history of the visual arts in each of these two countries has been formed and transmitted. Indeed, the authors of such works have established the timeline and refer to such a limited number of historical actors that it seems unlikely that these would be the only ones responsible for the emergence and institutionalization of the modern and contemporary art worlds. We support the assumption that an analysis of the literature and its evolution will offer a key to understanding the process by which the "glorious history" of the Algerian and Tunisian artistic movements was formed. We therefore propose to rethink the implementation of this dominant history by studying the process of writing art history.